(untitled) (Fiep Bulletin - online, 2014)
Obesity decreases the quality of life, as a result of which diseases increase the rate of morbidity and mortality. It markedly reduces the life time of people, especially when occurring already in children and youth. The aim of our work is to find out how BMI changes in the course of life of children and youth and to point to the fact that it will increase in the majority of children, when BMI was high already in the child´s age. Results of our research in 113 quizzes prove that in 10% of boys a gradual increase in BMI started from 6th up to 17th year of age was recorded, while in girls it was found in 20%. The highest incidence in boys is in the beginning of puberty, but in the period of „second height increase“, when paradoxically girls had frequent problems with obesity and overweight, these phenomena in boys begin to decline. Incidence of obesity and overweight is higher in girls when compared with boys. Acknowledgements: The contribution is a part of the grant project: VEGA 1/0478/11 „Prevention of obesity and functional disorders of the motor system and possibilities of their remedy in children and youth“